Analisis Pengaruh Tingkat Investasi, Pendapatan Asli Daerah dan Tenaga Kerja Terhadap PDRB Provinsi Jambi - Siti Marlina AZ; Siska Pebrina (Ekonomis: Journal of Economics and Business, 2019)
Economic development is the process of changing the undeveloped economic structure by means of capital investment and human investment aimed at increasing the prosperity of the population or rising income per capita. The purpose of this study was to find out about the effect of the level of investment, local revenue, labor on the GRDP of Jambi Province. In this study using qualitative and quantitative approaches. The variables used in this study are independent variables, namely the level of investment, Regional Original Income and labor. The dependent variable is Gross Domestic Regional Income. Data analysis tool used multiple regression, T test, F test and determination. The results of the research show that the investment level is still low due to high economic licensing. The level of investment, PAD and labor has a significant influence seen from the joint test, namely the determination of 11.036. In the end, research was targeted so that the economy of Jambi province increased by facilitating all processes in licensing activities and increasing PAD